Selection and use of stainless steels and nickel-bearing alloys in nitric acid - Schillmoller, C. M. (Technical series (Nickel Development Institute (Canada)) ;, 1992)
This publication examines the selection criteria for several stainless steels and nickel-bearing alloys in the production and handling of nitric acid and in its use, both in the production of ammonium nitrate fertilizers and as an acid mixture with HF for descaling.